Avaliaçao na Educaçao Física Escolar : a produçao audiovisual como ferramenta pedagógica para a aprendizagem - Frizzo, Giovanni; Correa da Silva, Patrícia (2018)
This article is the result of a study that aimed to analyze the audiovisual production as an instrument of pedagogical evaluation in the Physical Education (PE) classes of the final years of Elementary School. We performed an action-research in a school of the municipal public system of the city of Pelotas-RS in the discipline of PE in a class of the final years of the Elementary School. The research took place during a semester and the audiovisual production was used as the instrument of evaluation. The results showed that the experience of producing videos as a facilitator tool in the construction of knowledge is pedagogically efficient and, at the same time, it receives the student's recognition and approval, which presupposes that the insertion of ICT in education and the application of this new evaluative format contribute to the improvement of the teaching-learning process
O presente artigo é resultado de um estudo que objetivou analisar a produção audiovisual como instrumento de avaliação pedagógica nas aulas de Educação Física (EF) dos anos finais do Ensino Fundamental. Realizamos uma pesquisa-ação em uma escola da rede pública municipal da cidade de Pelotas-RS com a disciplina de EF, durante um semestre, em uma turma dos anos finais do Ensino Fundamental, utilizando como instrumento de avaliação do aprendizado a produção audiovisual. Os resultados evidenciaram que a experiência de produzir vídeos como mais uma ferramenta facilitadora na construção do conhecimento, além de ser eficiente pedagogicamente, teve o reconhecimento e aprovação dos estudantes, o que pressupõe que a inserção das TICs na educação e a aplicação deste novo formato avaliativo possa contribuir para melhoria do processo de ensino-aprendizagem
Keywords: Pedagogical evaluation; Pedagogical Work; Physical Education; Action-research; Pedagogical evaluation^lpt; Pedagogical work; Physical education; Action-research; Pedagogía; Estrategias de enseñanza; Material visual; Videograbación; Tecnología de las comunicaciones